SOCIO - ECONOMIC CHALLENGES OF WOMEN STREET VENDORS - Kyompaire, Patience (My University, 2011)
The research report assesses the socio economic challenges of women street vendors operating in the inner city of Johannesburg. The study was done to investigate the socio economic problems faced by the women street vendors as well as possible solutions to the problems were identified. The study was undertaken amongst other things to focus on the financial challenges, environmental challenges, policy implementation, and support from municipality structures. The study found out most of the women street vendors operate under strenuous conditions with continuous challenges most of which have endless solutions. The findings showed that most women street vendors face various financial, environmental, social and economic challenges as they ply their trade on streets. The researcher further concluded that most of the women street vendors had a low level of education, were independent, the achievements were uneven, lack of capital, high permit charges for the trading space, and lack of infrastructure were a major problem
MM - P&DM
Keywords: Street vendors; Informal traders